Isolasi dan Karakterisasi Bakteri Endofit Pelarut Fosfat dan Penghasil Hidrogen Cyanide (HCN) dari Tanaman Bawang Merah (Allium cepa L). - Wandita, Ryan Hilda; Pujiyanto, Sri; Suprihadi, Agung; Hastuti, Ratih Dewi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Onions (Allium cepa L.) is one of the leading horticultural commodities in Indonesia and is often used as seasoning and traditional medicine. Onion has a high economic value and fluctuating prices so that domestic onion production needs to be improved, one of them with a presence of endophytic bacteria that act as plant growth promoting agent or Plant Growth Promoting Bacteria (PGPB). Endophytic bacteria isolated from the root, leaves, and bulbs. In this research has been tested endophytic bacteria of onion plants from Garut regency which has PGPB factors such as able to dissolve phosphate, and produce HCN. The results obtained 251 isolates of endophytic bacteria. Based on the characterization results, the superior isolates capable of dissolving phosphate with an average diameter of 0.45 cm is isolate II.B.1D.3, and 11 isolates capable of producing high HCN. These isolates can be used as PGPB agents so that they can be useful in increasing plant growth and onion production and biocontrol in suppressing pathogens.Â Keywords: PGPB, endophyte, onion, phosphate, HCN